Overview of anaerobic corrosion of carbon steel radioactive waste packages in alkaline media in support of the Belgian supercontainer concept. Issue 1 (30th September 2020) - Kursten, Bruno; Smart, Nick R.; Senior, Nicholas A.; Macdonald, Digby D.; Caes, Sébastien; de Souza, Valdir; Gaggiano, Roberto
Abstract: The so‐called supercontainer concept is currently being considered as the reference design for the final disposal of vitrified high‐level radioactive waste and spent fuel in Belgium. It comprises a prefabricated Portland cement‐based buffer that completely surrounds a carbon steel overpack. In this highly alkaline environment (pH 13.6), and under normal conditions (i.e., without the ingress of aggressive species), the carbon steel overpack will be protected by a passive oxide film, which is expected to result in very low uniform corrosion rates. Considering the long timescales applicable to waste disposal, determining accurate and reliable estimates of the uniform corrosion rate under anoxic conditions forms a very important part of the safety and feasibility strategy. It is also crucial to demonstrate that no other form of corrosion apart from uniform corrosion takes place. This paper presents the progress of the research that has been made since the LTC2016 Workshop (Toronto, Canada) on uniform corrosion, pitting corrosion and stress corrosion cracking behaviour of P355 QL2 grade carbon steel exposed to an artificial concrete pore water solution. Abstract : The uniform corrosion, pitting corrosion and SCC behaviours of P355 QL2 grade carbon steel are investigated in a high pH concrete pore water solution under anoxic conditions. One of the findings suggest that pits cannot propagate under anoxic conditions because segmented pitting experiments showed that the pit walls become the cathode, whereas the external surface acts as the anode (i.e., polarity reversal).